Effect of administration of leptin on thyroid hormone in oxidative stress induced rats - Shaymaa Rabeea Madhkhoor1; Ihsan Raisan Ibrahim2 (Al-Qadisiyah Journal of Pure Science, 2018)
The aim of this study was to investigate the relationship between   exogenous leptin and thyroxin  on some stress types in  rats. In this study 60 male wistar albino rats were divided into two main groups (first was 5 day, and second was 10 day), each one subdivided into six groups (5 rat per subgroup):  Control And five treated groups ,which include: Leptin (10 Î¼g/kg leptin, sc. daily),  oxidative stress (0.5% H2O2),  leptin+ oxidative stress,   Diabetes, (induced by single injection of streptoztocin (65 mg/kg bw)), and  Leptin + diabetes.  At the end of the experiments the blood collected by cardiac   puncture under anesthesia. Plasma thyroxin and corticosterone  were measured. Our results showed that stress decreases  thyroxin level and increases  corticosterone  level, while leptin treatment reverse these changes.